First Record of Upeneus heterospinus Uiblein & Pavlov, 2019, Varied-Spine Goatfish (Syngnathiformes, Mullidae) from Terengganu, Malaysia, in the Southern Part of South China Sea - Noorhani Syahida Kasim,; Siti Tafzilmeriam Sheikh Abdul Kadir,; Seah, Ying Giat; Matsunuma, Mizuki; Tun Nurul Aimi Mat Jaafar,; Siti Azizah Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This is the first record of the varied-spine goatfish, Upeneus heterospinus Uiblein & Pavlov, 2019, in Malaysia. In March 2023, a single U. heterospinus specimen (70 mm standard length) was captured in Setiu Wetlands, Terengganu, Malaysia, in the southern part of South China Sea. Upeneus heterospinus has been recorded in southern Indonesia, Singapore, the Gulf of Thailand, Vietnam, the central Philippines, southern China, Taiwan, and Japan, but has not previously documented in Malaysian waters. Detailed morphometric and meristic specimen data are herein presented.